2020
DOI: 10.1007/s10597-020-00706-4
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Service Users’ Perceptions of Stigma, From the General Population and From Mental Health Professionals in Mexico: A Qualitative Study

Abstract: Negative attitudes towards people with mental health disorders have been widely studied and identified in the general population, and even within health care professionals. Moreover, studies focused on service users have also identified mental health professionals, including psychiatrists, as a source of stigma. However, in Mexico and Latin America few studies have been conducted addressing this issue. To explore mental health service users' perceptions of stigma by members of the general population and by psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Therefore, future studies should (Ho et al, 2020;Husain et al, 2020a, b). Mexico is a middle-income country with a relatively high incidence of mental disorders (Medina-Mora et al, 2003), where a low proportion of the population seeks mental health care and even fewer receive treatment (Heinze et al, 2019;Lagunes-Cordoba et al, 2021). Today, the issue of psychiatric illness continues to be stigmatized by our society, especially among doctors and medical students where the proportion of medical students with depression seeking treatment is very low (Puthran et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies should (Ho et al, 2020;Husain et al, 2020a, b). Mexico is a middle-income country with a relatively high incidence of mental disorders (Medina-Mora et al, 2003), where a low proportion of the population seeks mental health care and even fewer receive treatment (Heinze et al, 2019;Lagunes-Cordoba et al, 2021). Today, the issue of psychiatric illness continues to be stigmatized by our society, especially among doctors and medical students where the proportion of medical students with depression seeking treatment is very low (Puthran et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One important factor includes negative attitude or stigma, which is frequent among medical students [ 42 ]. Several studies found stigma to be a strong barrier to reach mental health services not only medical students but also all general mental health service users [ 43 47 ]. Stigma reduction is challenging, for the most effective way is still disputable [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, los participantes reconocen sus problemas de salud mental e incluso cómo repercuten en su vida cotidiana, en sus contextos y de manera personal, principalmente en lo afectivo, que coincide con el estudio de Berenzon et al (2014) al encontrar que las principales causas son las preocupaciones y la sensación de malestar emocional. Por tanto, los pocos universitarios que acuden a servicios de salud mental, son principalmente porque ya identifican un problema grave emocional y/o conductual, en este sentido, esta investigación encontró que hay universitarios con diagnósticos de ansiedad y depresión, trastornos de personalidad, y manifestaciones de tristeza, desesperanza, irritabilidad, soledad, y problemas familiares, económicos y sociales (Lagunes-Cordoba et al, 2020).…”
Section: Discussionunclassified